Deviatoric stress-induced transition of self-trapped exciton emissions - Chaofan Lv; Xigui Yang; Yanran Wu; Feihu Lei; Yachuan Liang; Dongwen Yang; Laizhi Sui; Jinxu Qin; Qilong Wu; Shoulong Lai; Hang Liu; Jinhao Zang; et al. (Nature Communications, 2025)
Abstract Self-trapped exciton (STE) emissions, featured by broad spectral band and minimal self-absorption, have garnered considerable attention for advanced lighting and imaging applications. However, developing strategies to facilitate multiple STE states, modulate the emission energy and extend the emission range remains a great challenge. Here, we introduce deviatoric stress to induce another intrinsic STE state (STE-2) and enable transitions between the intrinsic STE state (STE-1) and STE-2 in pyramidal ZnO nanocrystals. This approach results in a remarkable shift in emission energy, from yellow-green (2.34 eV) to deep-blue (2.88 eV). Combined in-situ stress monitoring and optical experiments show that the STE-2 state originates from a potential well generated by the deviatoric yield deformation of the pyramidal crystals under deviatoric stress. Spectroscopic and dynamical characterizations of the two STE emissions reveal a transition process in the carrier’s relaxation pathway from STE-2 to STE-1, and conversely at much higher pressures. These findings demonstrate that deviatoric stress serves as a robust tool for modulating STE emissions and provide new insights into the evolution of carrier dynamics of STE emissions.